Análisis de la percepción turística de los habitantes de la Parroquia La Unión del cantón Babahoyo para la implementación del turismo agroecológico - Valencia Lamilla, Erika Joselin (2020)
This case study is aimed at the analysis of the tourist perception of the inhabitants of the La Unión parish of the Babahoyo canton, for the implementation of Agroecological tourism. This research seeks to analyze the point of view and perspectives of the inhabitants. The perspectives are important to know if the inhabitants are or not, according to the tourist development in the area. The results were obtained through the research technique, which was the survey and its method is convenience sampling, it was decided to apply this method due to the emergency situation we are experiencing. The survey was applied to 100 people from the La Unión parish of the Babahoyo canton, between 25 and 65 years of age, to know their perceptions, from a tourist point of view. After the product of the analysis, it was concluded that the local community agrees with the tourism development in the area. Despite, that previously has not occurred. However, for reasons of being able to improve their quality of life and being able to have additional economic income, this has led them to appreciate the tourist phenomenon in a positive way.